2019
DOI: 10.3390/microorganisms7120686
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Immune Response Caused by Vector-Borne and Other Viral Infections in a Tupaia Model

Abstract: The Tupaia or tree shrew (Tupaia belangeri), a small mammal of the Tupaiidae family, is an increasingly used and promising infection model for virological and immunological research. Recently, sequencing of the Tupaia whole genome revealed that it is more homologous to the genome of humans than of rodents. Viral infections are a global threat to human health, and a complex series of events are involved in the interactions between a virus and the host immune system, which play important roles in the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In South Africa, a zoo puma tested positive for SARS-CoV-2 after coming in contact with an infected handler [30]. Tree shrews [31], a successful laboratory animal, were found to be susceptible to SARS-CoV-2 infection in an experimental setting [32]. A recent experimental infection in cattle revealed moderate susceptibility [6].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, a zoo puma tested positive for SARS-CoV-2 after coming in contact with an infected handler [30]. Tree shrews [31], a successful laboratory animal, were found to be susceptible to SARS-CoV-2 infection in an experimental setting [32]. A recent experimental infection in cattle revealed moderate susceptibility [6].…”
Section: Introductionmentioning
confidence: 99%
“…The tree shrew is an emerging experimental animal model with a higher degree of genetic similarity to primates than to rodents [33,101]. Previous studies have demonstrated that tree shrews are a promising animal model for several important viral infections in humans, including hepatitis B virus, hepatitis C virus, influenza virus, and ZIKV [59]. In an in vitro study, we showed the susceptibility of tupaia lung fibroblast cells to infection with all four DENV serotypes [58].…”
Section: Tree Shrew Modelmentioning
confidence: 75%
“…At this stage, the whole genome of the tree shrew has been sequenced, and because the neural, immune, and other systems of this species are similar to those of humans [53], this has led to the tree shrew being used in studies of different disease models, including depression [54], cancer [55], and viral infections [56]. In our work, the susceptibility to sindbis virus was also studied in the nervous system of the tree shrew.…”
Section: Discussionmentioning
confidence: 99%